Principals' Transformational Leadership Style in Public Senior Secondary Schools in Oyo State: Challenges and Prospects - Moses Adeleke Adeoye; Olaolu Paul Ainnubi (Nurul Jadid University, 2023)
The learning environment is greatly impacted by the leadership styles of principals, largely because of the fast-growing population and rising demand for high-quality education. Principals who choose transformational leadership can promote significant change and establish their schools as centres of excellence for learning and personal development as the global education landscape changes. The paper examines the opportunities and difficulties related to the transformational leadership approach used by principals in public senior secondary schools in Oyo State. The current state of transformational leadership practices among principals in public senior secondary schools in Oyo State was examined alongside the challenges they face and potential solutions. A comprehensive literature research was carried out to shed light on the advantages and challenges associated with the transformational leadership style of principals in Oyo State's public senior secondary schools. Based on the paper, principals encounter challenges such as resistance to change, resource constraints, teacher professional development, parent and community expectations and administrative obstacles while the prospects are cultural shift towards collaboration, creative resource management, empowered teacher leadership, community engagement and support and advocacy for educational reform. The Position Paper provides a more comprehensive and nuanced understanding of the challenges relating to transforming leadership in different learning environments, as well as an insight which can benefit education policymakers, administrators and researchers. In conclusion, this paper calls for collective efforts from all stakeholders in the education sector to promote and support transformational leadership in public senior secondary schools in Oyo State.